Revolutionizing Healthcare: The Role of Artificial Intelligence in Antibiotic Stewardship and Resistance Management - Alexandra Harry (Information Technology and Science (ITScience), 2024)
Artificial intelligence (AI) has great potential to transform the way antibiotics are managed in healthcare by providing creative ways to fight antibiotic resistance and enhance patient outcomes. This paper examines the various aspects of AI's function in the management of antibiotics, including diagnosis, tailored treatment, infection surveillance, and future implications. The talk focuses on the potential advantages of AI-driven methods, such as improved diagnostic precision, customized treatment plans, and proactive monitoring of patterns of antibiotic resistance. But there are several obstacles to overcome before AI can be fully applied in the healthcare industry. These include issues with technical complexity, data accessibility and quality, clinical acceptability, regulatory concerns, and long-term financial viability. Collaboration amongst partners, financial support for infrastructure and resources, and a dedication to moral, patient-centered care are all necessary to meet these obstacles. Notwithstanding these challenges, AI-driven antibiotic management has enormous potential to revolutionize global patient outcomes, fight antibiotic resistance, and change healthcare delivery.